Evaluation of Imported Clones of Washington navel oranges Grafted On Citrumelo 4475. - مخول, جرجس; الخطيب, علي; يونس, علا (Latakia University Journal -Biological Sciences Series, 2021)
The study was conducted in Ciano citrus research station, belonging to the Agricultural Scientific Research Center In Lattakia during the 2018 and 2019 seasons ; in order to evaluate some imported clones of Washington navel oranges grafted on Citrumelo 4475. Growth characteristics were studied (tree height, canopy height, canopy size), growth cycles, fruit set, fruit diameter, weight and size, in addition to the size and weight of the juice, Peel and pulp thickness, the chemical properties of the juice were also studied (Total soluble solids, Total acids, vitamin C content). Statistical analysis showed the superiority of Washington navel 204 in yield (232.5 kg/ Tree), fruit weight (264.67 g) and fruit size (301.3 cm3), weight of the juice (64.16 g) and juice ratio (24 %) and vitamin C ratio (33.4 mg/100 ml juice ). No significant differences were found among the clones Grafted on Citrumelo 4475 in Total soluble solids level ; While Total acids level increased in Washington navel 205 (0.82).